Plasmonic silicon nanowires for enhanced heat localization and interfacial solar steam generation - Joo, Beom Soo; Kim, In Soo; Han, Il Ki; Ko, Hyungduk; Kang, Jin Gu; Kang, Gumin (Elsevier BV, 2022)
Solar-thermal energy conversion for passive steam generation is attracting a lot of attention as a next-generation eco-friendly and sustainable technology. Tremendous effort has been devoted to produce efficient light absorbing materials such as metal nanoparticles, semiconductors, MXene, and carbon-based materials. Among the various candidates, silicon (Si) is an excellent light-absorber that has been widely used in solar power generation. However, Si barely absorbs photons that have energy below its bandgap (1.12 eV), which occupies 20% of the entire solar spectrum. Here, we propose a metal-Si hybrid nanowire (NW) structure (plasmonic Si NWs) suitable for overcoming the low absorption limit of Si. The bundle-shaped Si NWs involving plasmonic nanostructures exhibits strong light absorption properties (A(avg) > 91%) over the entire solar spectrum (300-2500 nm). The low thermal conductivity of Si NWs enhance heat localization by suppressing the heat dissipation to the surrounding. Owing to the unique optical and thermal properties of the plasmonic Si NW structure, excellent evaporation rates and efficiencies of 1.12 kg m(-2)h(-1) and 72.8 %, respectively, were obtained under 1-sun illumination (1 kW m(-2)). Thus, the plasmonic Si NWs have the potential to be used in various fields such as solar photothermal desalination, contaminated water purification, and solar thermoelectric power generation.